2006
DOI: 10.1111/j.1460-9568.2006.04768.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid phosphorylation of histone H2A.X following ionotropic glutamate receptor activation

Abstract: Excessive activation of ionotropic glutamate receptors increases oxidative stress, contributing to the neuronal death observed following neurological insults such as ischemia and seizures. Posttranslational histone modifications may be key mediators in the detection and repair of damage resulting from oxidative stress, including DNA damage, and may thus affect neuronal survival in the aftermath of insults characterized by excessive glutamate release. In non-neuronal cells, phosphorylation of histone variant H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 60 publications
8
72
0
Order By: Relevance
“…Note that presence of γH2A.X could also be involved in mitosis and meiosis, neural development, and neurogenesis in the adult brain [5052]. The formation of γH2A.X is associated with cell cycle suspension in proliferating cells [29], as well as NMDA/AMPA receptor stimulation in differentiated neuronal cells [53]. Finally, the presence of γH2A.X predicts neuronal endangerment and death following a pathological state in the adult brain [54].…”
Section: Discussionmentioning
confidence: 99%
“…Note that presence of γH2A.X could also be involved in mitosis and meiosis, neural development, and neurogenesis in the adult brain [5052]. The formation of γH2A.X is associated with cell cycle suspension in proliferating cells [29], as well as NMDA/AMPA receptor stimulation in differentiated neuronal cells [53]. Finally, the presence of γH2A.X predicts neuronal endangerment and death following a pathological state in the adult brain [54].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, phosphorylation of histone H2A.X (γ-H2A.X) occurs 'generically' after DNA damage (Rogakou et al, 1998), but the same is also observed under physiologically unique circumstances, e.g. stimulation of the inotropic glutamate receptors in cortical neurons (Crowe et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that, while neurons might have decreased NeuN antigenicity when under stress, the cells used in our experiments would not be under toxic or stressed conditions. While our plating medium did contain 25 M glutamate, which is typical of many primary neuronal culture protocols (for example, Hruska-Hageman et al, 2002;Cole et al, 2005;Crowe et al, 2006), this would not have caused neuronal injury. First, the astrocytic component of the component would have served to reduce medium glutamate concentration; Ye and Sontheimer (1998) showed that confluent astrocyte cultures can reduce the concentration of glutamate in medium from 85 to <1 M in 2-3 h. Therefore it is likely that the glutamate concentration would already have been low by the time the medium was changed to the maintenance medium, which was glutamate free, after 3 days.…”
Section: Discussionmentioning
confidence: 99%